Empirical Study on the Effectiveness of Network-based College English Teaching Mode - chengxing, Jin (International Journal of Emerging Technologies in Learning (iJET), 2013)
In order to study the effectiveness of the network-based college English teaching mode, the paper firstly introduces the application background, its main features and theoretical basis. Then, an investigation via questionnaires was made to the two experiment classes and studentsâ?? achievement test scores were compared between the two experiment classes and the control class. By analyzing the findings and comparing the achievement test scores, a conclusion was arrived that the students in the experiment classes benefits by developing an autonomy in English learning, getting highly motivated , becoming more independent of teachers and, more importantly, their comprehensive abilities were more enhanced , particularly in listening ,speaking, reading and writing, while, on the other hand, teachers are still an important factor, acting its new role by designing the courseware, administrating studentsâ?? autonomous learning, facilitating the learning process ,organizing the cooperative learning activities and giving instructions on using the network resources and learning strategies.